Effect of exercise intensity and mode on acute appetite control in men and women - Panissa, Valï¿½ria Leme Gonï¿½alves; Julio, Ursula Ferreira; Hardt, Felipe; Kurashima, Carolina; Lira, Fï¿½bio Santos [UNESP]; Takito, Monica Yuri; Franchini, Emerson (Canadian Science Publishing, 2016)
The aim of this study was to compare the effects of exercise intensity on appetite control: relative energy intake (energy intake minus the energy expenditure of exercise; REI), hunger scores, and appetite-regulating hormones in men and women. Eleven men and 9 women were submitted to 4 experimental sessions: high-intensity intermittent all-out exercise (HIIE-A) for 60 ï¿½ 8 s interspersed by 12 s of passive recovery; high-intensity intermittent exercise (HIIE) at 100% of maximal load attained in incremental test; steady-state exercise at 60% of maximal load, matched by work done; and a control session. Exercise was performed 1.5 h after a standardized breakfast, and an ad libitum lunch was offered 4 h after breakfast. Blood concentration of insulin, cortisol, acylated ghrelin, peptideYY3-36, glucose, and hunger scores were measured when fasting, and at 1.5, 2, 3.25, and 4 h of experiment. REI was lower in all exercises than in the control, without differences between exercises and sex showing no compensation in energy intake because of any exercise; the hunger scores were lower only in the exercises performed at higher intensity (HIIE and HIIE-A) compared with the control. The area under the curve of acylated ghrelin was lower in the HIIE-A when compared with the control. PeptideYY3-36 was higher in men than women and cortisol higher in women than men independently of the condition. Although high-intensity exercises promoted a little more pronounced effects in the direction of suppressing the appetite, no differences were observed in REI, demonstrating that these modifications were not sufficient to affect energy intake.
Keywords: Appetite-regulating hormones; Energy intake; High-intensity intermittent exercise; Hunger; Sex